Application of Low-Frequency Raman Scattering Spectroscopy to Probe in Situ Drug Solubilization in Milk during Digestion - Salim, Malinda (J Phys Chem Lett, 2019)
[Image: see text] We have recently shown that real-time monitoring of drug solubilization and changes to solid state of the drug during digestion of milk can be achieved using synchrotron small-angle X-ray scattering. A complementary laboratory-based method to explore such changes is low-frequency Raman spectroscopy, which has been increasingly used to characterize crystalline drugs and their polymorphs in powders and suspensions. This study investigates the use of this technique to monitor in situ drug solubilization in milk during the process of digestion, using a lipolysis model/flow-through configuration identical to that used previously for in situ synchrotron small-angle X-ray scattering studies. An antimalarial drug, ferroquine (SSR97193), was used as the model drug for this study. The Raman spectra were processed using multivariate analysis to extract the drug signals from the milk digestion background. The results showed disappearance of the ferroquine peaks in the low-frequency Raman region (<200 cm(–1)) after approximately 15–20 min of digestion when milk fat was present in the system, which indicated drug solubilization and was in good agreement with the in situ small-angle X-ray scattering measurements. This proof-of-concept study therefore suggests that low-frequency Raman spectroscopy can be used to monitor drug solubilization in a complex digesting milk medium because of the unique vibrational modes of the drug crystal lattices.